Compounded hydrocortisone preparations for children with congenital adrenal hyperplasia: are they safe ? - Rooman, Raoul (Belgian Journal of Paediatrics, 2023)
Children with congenital adrenal hyperplasia (CAH) or adrenal insufficiency (AI) need hydrocortisone and sometimes fludrocortisone in appropriate doses to survive. Low dose hydrocortisone preparations and fludrocortisone are not commercially available on the Belgian market so pediatricians have to rely on tablet splitting or crushing and pharmacy compounding. These methods can create substantial dosage errors with important clinical implications and are not subject to the quality controls and pharmacovigilance requirements that govern approved drug preparations. In addition, repeated supply shortages of the active pharmaceutical ingredients have occurred in the last years. Commercial low dose hydrocortisone and fludrocortisone products and modified-release hydrocortisone preparations, reliably produced under GMP regulations, could improve the safety risk associated with compounded medication but are not yet available in Belgium.